Employment Opportunities for the Certificate Holders: an Analysis of New Social Milieu in the Context of Banking Sector of Pakistan - Mahmood, Babak; Saba, Ayesha; Khaliq, Mehreen; Hussain, Shabbir (Richtmann Publishing, 2011)
The study was conducted to evaluate the importance of banking diploma of IBP (Institute of bankers of Pakistan). Likewisethe study also focused on the employment benefits for IBP certified individuals. As in consideration about this study IBP certification wasindependent variable and dependency of employment opportunities were checked upon independent variable. Many intervening variables forinstance opportunities of being promoted, high banking insight, knowledge of banking laws and diversified skills were studied carefully forthe purpose of getting beneficial results This research was based on quantitative approach and for the sake of getting knowledge aboutworth of IBP diploma study was conducted in diversified banks by selecting people randomly from each bank. A sample of 100 peoplewas selected and a structured questionnaire based on likert scale was developed and data was collected from different branches of banks.Descriptive (mean, standard deviation) and inferential statistics (Bi- variate analysis) were applied for data analysis.Findings showedthat IBP diploma has great significance for banks and IBP certified people are preferred by most of the banks including private,government, Islamic and non Islamic banks. Bi-variate analysis showed that with completion of each stage of IBP certification, level of jobopportunities in banking sector is increased for IBP certified people. This study emphasized that In Pakistan IBP certification is of greatimportance and its benefits are numerous in banking sector of Pakistan with regard to job opportunities. This certification IBP instituteprovide sound basis for getting good jobs in all types of banks of Pakistan.